Az újrajátszás romlékonysága: Kis Varsó munkája Debrecenben - Zuh, Deodáth (Studia Litteraria, 2024)
This paper revisits the artist duo Little Warsaw (Kis Varsó), and their work titled Marble Street, recently re-exhibited at MODEM in Debrecen. I aim to point to their relevance for the theory of artistic re-enactment, which could not prevail to the naked eye. In my interpretation, Marble Street plays on the sacral element of the relocation of buildings, and in doing so, not only assesses the preservation of material heritage but equally seeks to adumbrate the community-building power of regular commemoration. e relocation of buildings seems to be a relevant matter of engineering, preservation, and rehabilitation. Yet, it has a role similar to that of religious processions in countries (e. g. Romania) where the objects to be moved were themselves sacral structures, and dealing with them raised and still raises the question of attachment to the cultural homeland. In the Hungarian context, the Little Warsaw experiment gains specific pertinence for the relocation of built structures eluded local urban planning under socialism. Consequently, the quasi-sacral aspect of moving mid-size objects could not be registered in the minds of the observers.